Religious Character Strengthening As Children Policy at SDIT Faza Azkia - Fata, Nahriyah; Hakam, Kama Abdul; Somad, Momod Abdul; Ruyadi, Yadi (PrimaryEdu : Journal of Primary Education, 2023)
The negative and positive impacts of the spread of digital as one of the main characteristics of changes in welcoming the 4.0 revolution era turned out to have a major impact on the process of parenting children in the family. This study aims to determine the effectiveness of strengthening religious character in children at one of the schools, namely Sdit Faza Azkia. This research uses a qualitative approach with a case study method. Data collection techniques used in this study were observation, interviews and questionnaires related to students' opinions regarding the application of policies on childcare. The results of the study show that the use of the method of strengthening religious character is effective as one of the parenting patterns as implemented at SDit Faza Azkia.